2020
DOI: 10.1111/ppe.12671
|View full text |Cite
|
Sign up to set email alerts
|

Global trends in incidence rates of childhood liver cancers: A systematic review and meta‐analysis

Abstract: Background Childhood liver cancers are relatively rare, hence inferences on incidence trends over time are limited by lack of precision in most studies. Objective To conduct a systematic review and meta‐analysis of published contemporary trends on childhood liver cancer incidence rates worldwide. Data sources PubMed, EMBASE, CINAHL, Web of Science. Study selection and data extraction English‐language peer‐reviewed articles published from 1 January 2008 to 1 December 2019 that presented quantitative estimates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
(107 reference statements)
1
6
0
Order By: Relevance
“…Liver cancer continues to remain a global burden, with incidence rates increasing across all ages 31,32 . Results from the current study have confirmed observations from other epidemiological studies noting the increasing incidence of hepatic cancers in children 33‐36 …”
Section: Discussionsupporting
confidence: 88%
“…Liver cancer continues to remain a global burden, with incidence rates increasing across all ages 31,32 . Results from the current study have confirmed observations from other epidemiological studies noting the increasing incidence of hepatic cancers in children 33‐36 …”
Section: Discussionsupporting
confidence: 88%
“…The probability of hepatoblastoma occurring in an infant or young child varies between 0.5 and 2 cases per million children per year. The explanation for this vast difference could be due to differing age groups and the possibility that the low hepatoblastoma values given in recent individual publications originate from "old" statistics, and therefore no longer accurately depict current incidence rates (29,30). Regional peculiarities supposedly play a subordinate role (25).…”
Section: Epidemiologymentioning
confidence: 99%
“…Retinoblastoma is often diagnosed and treated in specialized (ophthalmology) clinics, which are sometimes missed as data sources. The increase in incidence of hepatic tumors among males has been described; however, the reasons are unclear ( 33 ). The considerable increase in the incidence of bone tumors among males in SA may be the result of better diagnosis and would be consistent with the decreasing trend of unspecified tumor types and no increase seen in females, who also undergo growth spurt just before males.…”
Section: Discussionmentioning
confidence: 99%